Characterization of chemical composition variations in raw and processed Codonopsis Radix by integrating metabolomics and glycomics based on multiple chromatography‐mass spectrometry technology. Issue 13 (18th May 2022) - Wang, Yan; Zhang, Jing‐jing; Wang, Zi‐xia; Cui, Fang; Zhang, Qian‐Nian; Song, Ping‐ping; Li, Bing; Tang, Zhuo‐shi; Hu, Fang‐di; Shi, Xiao‐feng
Abstract : Codonopsis Radix, a popular food homology medicine, is widely used in clinical traditional Chinese medicine and food supplement, raw products and three types of processed products are the main forms of decoction pieces in China. However, there is no scientific basis for comprehensive chemical characterization of raw and three types of processed products. Herein, we investigated qualitatively and quantificationally secondary and primary metabolites in raw Codonopsis Radix and three types of processed products by metabolomics and glycomics employing multiple chromatography‐mass spectrometry technology combined with chemometric analysis further to look for differential compounds and propose the processing‐induced chemical mechanisms. The results indicated that Codonopsis Radix became dark‐colored and the smell of burnt incense odor was observed after processing. The principal component analysis demonstrated that secondary metabolome and glycome were significantly altered between raw and processed products, and 36 differential secondary metabolites and 11 differential primary metabolites were finally screened through orthogonal partial least‐squares‐discriminant analysis. The main types of compounds are alkaloids, terpenoids, glycosides, amino acids, monosaccharides, oligosaccharides, and furfural derivatives. Meanwhile, Chemical mechanisms could be involved, including oxidation, glycosidic hydrolysis, esterification, dehydration, and Maillard reaction. This work supplies a chemical basis for the application of various types of Codonopsis Radix decoction pieces.